PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN PADA PRODUK 3 SECOND DI JAKARTA BARAT - Muksalmina, Muksalmina; Kramadibrata, Budi Santosa (Jurnal Riset Rumpun Ilmu Ekonomi, 2023)
The development of business in the current era is very promising, there are many opportunities and challenges for a company. Companies will compete with each other to be able to meet consumer needs, thus companies must be able to compete with other companies so that they can survive the competition that occurs Along with the times that have entered the Asean Economic Community (AEC), the era of globalization has resulted in many new businesses emerging which can lead to competition figures, quantitative research is research based on empirical philosophy with statistical data analysis with the aim of explaining and selling hypotheses. The researcher chose this type of quantitative research because he wanted to know and prove the effect of product quality and service quality on customer satisfaction 3Second in West Jakarta. This study used an associative design which can be used to see the effect of two or more variables. Based on the f testing criteria it can be seen that the significant value is 0.000 or less than 0.05, it can be stated that there is a significant simultaneous influence on promotion (X1) and product quality (X2) on purchasing decisions (Y). Brand image has a significant effect on product quality. On the results of the t test, a significant value of the brand image variable was obtained at 0.000 ± 0.05, which means that brand image has a significant effect on consumer satisfaction. Product quality has a significant effect on product satisfaction 3seconds. In the results of the t test, a significant value of the product quality variable is obtained at 0.000 0.05, which means that product quality has a significant effect on consumer satisfaction.